1996
DOI: 10.1080/00958964.1996.9941466
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Affect, and the Environment: 15 Years of Research (1979–1993)

Abstract: The current review examined the relationship among knowledge, affect, and environmental education that has emerged in the last 15 years from research on classroom-type settings and applications. Despite methodological and statistical problems, an association between knowledge and affect has surfaced, , along with prominent sex differences and a suggestion of ethnic variation. However, the nature of this relationship is still unclear. Given that both knowledge and affect are necessary for active participation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1
8

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 18 publications
4
13
1
8
Order By: Relevance
“…In this study there were no significant gender differences found in environmental knowledge, however other studies have reported gender differences, with males scoring higher in environmental knowledge (Chawla, 1998; Coyle, 2004; Kollmuss & Agyerman, 2002; Tikka et al, 2000; Zimmerman, 1996). There were also no significant differences found in self‐reported behaviors or comfort levels.…”
Section: Discussioncontrasting
confidence: 83%
“…In this study there were no significant gender differences found in environmental knowledge, however other studies have reported gender differences, with males scoring higher in environmental knowledge (Chawla, 1998; Coyle, 2004; Kollmuss & Agyerman, 2002; Tikka et al, 2000; Zimmerman, 1996). There were also no significant differences found in self‐reported behaviors or comfort levels.…”
Section: Discussioncontrasting
confidence: 83%
“…However, 'awareness' of what remains a problem. According to a review of environmental knowledge and affect by Zimmerman (1996), knowledge and affect are related. We simply don't know how.…”
Section: Methodological Approachmentioning
confidence: 99%
“…When compared with control data, data from students receiving the educational module showed significant increases in NEP endorsement that declined somewhat with time but remained significantly greater after 3 semesters. In contrast, retention of knowledge from the module showed a predictable decrease over time.KEY WORDS: environmental attitudes, NEP scale, environmental awareness he emerging concerns of both local and global environmental problems over the past several decades have given rise to a broad array of educational programs in primary and secondary schools (e.g., Leeming, Dwyer, Porter, & Cobern, 1993;Rickinson, 2001;Zimmermann, 1996). The implicit goal of such programs has been to create an electorate that is better informed on environmental issues and, thus, better able to make appropriate decisions that have an effect on ecological problems.…”
mentioning
confidence: 99%